Determination of Activity Relationship Chart (ARC) Method in Office Layout Evaluation: A Case Study at XYZ Bandung Apartment - Ayi Tejaningrum; Gita Muthia Hasna (AIBPM Publisher, 2024)
XYZ Apartment Bandung has 12 departments located from the lobby floor to the fourth basement floor. The apartment has an office layout that is not yet optimally arranged, such as the placement of departments that are far apart, ineffective handling of goods, and the risk of work accidents. The purpose of this study is to improve the existing layout so that the comparison results can be seen between before and after the improvement. A survey of 56 employees and managers was conducted to gather data on department relationships. The ARC (Activity Relationship Chart) method was employed to analyze these relationships and inform layout optimization. Based on the results of the analysis, there was a change in department placement that resulted in an efficiency of travel distance of 64.3% and time efficiency of 64.4%. The findings emphasize the importance of optimizing workspace layout to enhance operational efficiency and employee satisfaction. Implementing the proposed layout changes can lead to cost savings, increased productivity, and improved employee well-being within XYZ Bandung Apartment.